2020
DOI: 10.3390/biom10020192
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of VX-Inhibited Human Acetylcholinesterase by Deprotonated Pralidoxime. A Complementary Quantum Mechanical Study

Abstract: In the present work, we performed a complementary quantum mechanical (QM) study to describe the mechanism by which deprotonated pralidoxime (2-PAM) could reactivate human (Homo sapiens sapiens) acetylcholinesterase (HssAChE) inhibited by the nerve agent VX. Such a reaction is proposed to occur in subsequent addition–elimination steps, starting with a nucleophile bimolecular substitution (SN2) mechanism through the formation of a trigonal bipyramidal transition state (TS). A near attack conformation (NAC), obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We were pleased to find that by selecting various docking techniques, such as free flexible docking, flexible docking with distance constraints, and covalent docking, we obtained promising results that allowed us to conduct a comprehensive analysis of OP–reactivator–cholinesterase interactions. Many groups involved in research on the reactivation of cholinesterases focus on an important stage in the reactivation process: the moment when the reactivator adopts a prereactivation pose [ 20 , 41 , 44 ]. Based on the reactivation cycle presented by Allgardsson et al [ 20 ] in which the reactivator can adopt nonreactivation or prereactivation conformations at the active site of OP-blocked cholinesterase, we performed an interaction analysis for five known reactivators modeling both states at AChE and BuChE active sites blocked by sarin or tabun.…”
Section: Discussionmentioning
confidence: 99%
“…We were pleased to find that by selecting various docking techniques, such as free flexible docking, flexible docking with distance constraints, and covalent docking, we obtained promising results that allowed us to conduct a comprehensive analysis of OP–reactivator–cholinesterase interactions. Many groups involved in research on the reactivation of cholinesterases focus on an important stage in the reactivation process: the moment when the reactivator adopts a prereactivation pose [ 20 , 41 , 44 ]. Based on the reactivation cycle presented by Allgardsson et al [ 20 ] in which the reactivator can adopt nonreactivation or prereactivation conformations at the active site of OP-blocked cholinesterase, we performed an interaction analysis for five known reactivators modeling both states at AChE and BuChE active sites blocked by sarin or tabun.…”
Section: Discussionmentioning
confidence: 99%
“…From these calculations, the energetic barrier of the reactivation process of each enzyme–OP complex with trimedoxime was determined. This theoretical strategy has been previously employed in other works [ 26 , 38 , 39 , 40 , 41 , 42 , 43 ]. The QM part of the calculations was performed through the Gaussian 09 package, at the DFT level and 6-31g(d,p) basis set [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Treatments for general nerve agent and insecticide poisoning have utilized oxime derivatives as well. Reactivation of a VX-AChE complex using a deprotonated pralidoxime, or 2-pralidoxime (2-PAM), occurs through consecutive addition-elimination steps and shows promising results as an antidote [ 166 ]. Docking and QM/MM methods paired with experimental observations revealed that trimedoximes show potential to reactivate Mus musculus AChE, with the AChE-VX complex showing the best results [ 167 ], and MD simulations of 2-PAM with phosphorylated AChE support this claim [ 168 ].…”
Section: Inhibitionmentioning
confidence: 99%